"If she wants to eat…and eat and eat…fine! It's gonna feed the baby": Pregnant women and partners' perceptions and experiences of pregnancy with a BMI >40 kg/m2. (June 2017) - Keely, Alice; Cunningham-Burley, Sarah; Elliott, Lawrie; Sandall, Jane; Whittaker, Anne
Abstract: Introduction: women with a raised BMI are more likely to gain excessive weight in pregnancy compared to women with a BMI in the normal range. Recent behaviour change interventions have had moderate to no influence on GWG, and no effect on other perinatal outcomes. Evidence is required regarding the social and cultural contexts of weight and pregnancy. No studies to date have included the views of partners. Aims: to explore the experiences, attitudes and health-related behaviours of pregnant women with a BMI >40 kg/m 2 ; and to identify the factors and considerations which shape their beliefs, experiences and behaviours, and how these may change during and after pregnancy. 2. To determine the impact, if any, of the beliefs and attitudes of significant members of the women's families and social networks upon the women's experiences, attitudes and health-related behaviours in relation to weight and pregnancy Methods: this was a prospective serial interview study. Semi-structured interviews were conducted with 11 pregnant women with a BMI >40 kg/m 2, during pregnancy and after birth, and once with 7 partners (all male) of women. Interview questions were designed to be appropriately but flexibly framed, in order to explore and gather data on participants' everyday life, lifestyles, views, experiences, relationships and behaviours, focussing more specifically on beliefs about health, pregnancy, weight and diet. Thematic content analysis was used to formally analyse and unearth patterns in the data. Findings: the findings can be grouped into six interrelated themes: the complexities of weight histories and relationships with food; resisting risk together; resisting stigma together; pregnancy as a 'pause';receiving dietary advice; postnatal intentions. These themes are interrelated due to the 'spoiled identity' (Goffman, 1963) that the large body represents in western culture and related stigma. Conclusion and implications: this study provides evidence that there exist deeply ingrained social and cultural beliefs among women and in particular their partners, regarding pregnancy diet and weight gain. Further, this study provides evidence that male partners may resist stigmatised risk on behalf of a pregnant partner. All women (and several men) expressed an intention to adopt healthy behaviours and lose weight once their baby was born. Further evidence is required regarding the means by which women who experience stigmatised risk during pregnancy, and their partners, might be engaged and receptive to health advice. Models which draw on ideals of relationship-centred care, and selfefficacy via open discussion with women and families, engaging women and partners by providing them with an opportunity to talk about their beliefs and concerns, could be explored to inform future research and practice. Highlights: Couples took part in interviews to explore pregnancy experiences with a BMI >40 kg/m 2 . Couples provided concurring accounts to resist stigma and preserve moral integrity. Couples used strategies to normalise weight and to negotiate and neutralise risk status. An intention to lose weight following birth was expressed by all participants. Pregnancy was viewed as a 'pause' with a focus on future health, including that of their children.